CORPORATE CULTURE IN THE IMPLEMENTATION OF THE ENTERPRISE DEVELOPMENT STRATEGY - Zapukhliak, Ivanna Bogdanivna (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2021)
The relevance of the study of corporate culture as a tool for implementing the strategy of enterprise development is substantiated. Approaches to the interpretation of the concept of "corporate culture" are considered, which allowed to outline the elemental composition of corporate culture, identify sources of culture at the enterprise level, highlight its most important characteristics and prove the importance of corporate culture in implementing enterprise development strategy. The system of interconnections and interrelations through which the type of corporate culture at the enterprise is formed is found out. It is proved that the harmonization of corporate culture and strategy of the enterprise is an effective tool to ensure its further development. Methods of corporate culture diagnostics are considered and using the OCAI method, the type of corporate culture is determined on the example of a higher education institution, the directions of its improvement are revealed in terms of harmonization of the institution’s strategy and elements and style of its corporate culture market of educational services. Corporate culture is presented as a system of personal and collective values, which, under ideal conditions, are accepted and shared by all members of the enterprise, and practically implemented through a set of norms, techniques, rules for solving problems of external adaptation and internal integration of employees. It is determined that the main purpose of the corporate culture of the enterprise is to harmonize its elements with the development strategy of the enterprise to ensure its sustainability and competitiveness. It is proved that the development of corporate culture of the university is an important aspect to solve existing problems and to ensure its success. In particular, further research should be developed in the context of developing specific tools and measures to change the type of corporate culture as a whole at the university and its individual components, which will practically achieve the strategic goals and ensure a competitive position in the market of educational services.